FEATURES OF EQUIPMENT FOR CENTRIFUGAL CASTING AND TECHNOLOGY OF OBTAINING BLANKS - D. V. Zanko; S. V. Levchuk; A. N. Saharevich (Литьë и металлургия, 2012)
The features of equipment for centrifugal casting are considered. Advantages and disadvantages of centrifugal casting machines.